2016
DOI: 10.1097/mpg.0000000000001136
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokeratin‐18 Level As a Novel Biomarker for Liver Fibrosis in Children With Nonalcoholic Fatty Liver Disease

Abstract: CK18 is a promising noninvasive biomarker for fibrosis in NAFLD in children. A fibrosis prediction model that includes CK18 and waist circumference percentile should be validated in other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 39 publications
2
38
0
1
Order By: Relevance
“…Therefore, we used CK-18 fragment as a surrogate of the severity of liver injury and fibrosis. 23,24 In conclusion, the present study confirms PNPLA3, GCKR and…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Therefore, we used CK-18 fragment as a surrogate of the severity of liver injury and fibrosis. 23,24 In conclusion, the present study confirms PNPLA3, GCKR and…”
Section: Discussionsupporting
confidence: 87%
“…We surely cannot perform liver biopsy as a screening method in the general population. Therefore, we used CK‐18 fragment as a surrogate of the severity of liver injury and fibrosis …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CK18 M30 level is also correlated with fibrosis in children with NAFLD 32 . Other studies also found in patients with chronic hepatitis C, M30 is associated with fibrosis instead of steatosis 33 .…”
Section: Discussionmentioning
confidence: 92%